Implementasi Media Pembelajaran Dengan Macromedia Flash Untuk Meningkatkan Kemampuan Pemahaman Matematis Mahasiswa - Setiyani, Setiyani; Santi, Dina Pratiwi Dwi (Pendidikan Matematika Universitas PGRI Yogyakarta, 2019)
AbstractThis research aims to find out the improvement of students' understanding of concepts in the basic mathematics subject of relations and functions. This type of research is an experiment, with one group pretest-posttest design research design. The study population was all first-level students of the Primary School Teacher Education Program (PGSD). The determined sample is class I.A as many as 26 students with a purposive sampling technique. Research instruments in the form of UTS questions and tests of students' conceptual understanding. Testing this hypothesis using the t-test. Before conducting a hypothesis test, first test the normality and homogeneity. The student group is divided into three categories, namely high, low, and medium based on UTS results. Furthermore, based on the normalized gain score test obtained an increase in the ability of mathematical understanding for groups of students who have high and medium ability with sufficient criteria. While the group of students who have low ability has an increase with low criteria. Overall the implementation of learning media using Macromedia flash can improve students' mathematical understanding abilities by 0.403, including enough categoriesKeywords: Macromedia Flash, Relationships and Functions, Mathematical Understanding